PELATIHAN PRODUCT BRANDING SEBAGAI OPTIMALISASI STRATEGI PEMASARAN BAGI UMKM - Mahfirah, Titis Fatarina; Rahmi; Haneul; Haura, Tazkia; Putri, Clara Alika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The importance of small and medium enterprises (SMEs) for the Indonesian economy has become an important concern. Especially during the COVID-19 pandemic, SMEs in Indonesia has experienced an increase and has become the most stable sector while other businesses, including large companies, have been affected by COVID-19. However, as SMEs increases, competition also increases. To help SMEs compete in the market, innovation such as building branding is needed. However, many MSMEs have not mastered the application of branding in their business. To this end, product branding training is organized for SMEs trained by Suku Dinas PPKUKM Kota Administrasi Jakarta Timur. This training is an implementation of cooperation between the S1 Management Study Program Faculty of Economics Universitas Negeri Jakarta and Suku Dinas PPKUKM Kota Administrasi Jakarta Timur. The training is conducted online using the Zoom platform. The implementation of the activity begins with the preparation stage, the implementation stage, activity evaluation, reporting and publication of activity outcomes. As a result, SMEs understand the importance of branding for their business. In addition, SMEs are also able to determine the branding strategy that they will implement in their business. Abstrak Tingginya peranan UMKM untuk perekonomian Indonesia menjadi perhatian penting. Terlebih pada saat pandemi COVID-19, UMKM di Indonesia mengalami peningkatan dan menjadi bidang yang paling stabil disaat usaha sektor lain termasuk perusahaan besar goyah akibat adanya COVID-19. Namun, dengan meningkatnya UMKM tentu persaingan ikut meningkat. Untuk membantu UMKM bersaing di pasarnya, diperlukan inovasi seperti membangun branding. Namun, banyak pelaku UMKM yang belum menguasai penerapan branding dalam usaha mereka. Untuk itu, diselenggarakan pelatihan mengenai product branding bagi UMKM yang dibina oleh Suku Dinas PPKUKM Kota Administrasi Jakarta Timur. Pelatihan ini merupakan implementasi kerja sama antara Program Studi S1 Manajemen Fakultas Ekonomi Universitas Negeri Jakarta dengan Suku Dinas PPKUKM Kota Administrasi Jakarta Timur. Pelatihan dilaksanakan secara daring menggunakan platform Zoom. Pelaksanaan kegiatan diawali dengan tahap persiapan, tahap pelaksanaan, evaluasi kegiatan, pelaporan dan publikasi luaran kegiatan. Hasilnya, pelaku UMKM memahami pentingnya branding untuk usaha mereka. Selain itu, pelaku UMKM juga mampu untuk menentukan strategi branding yang akan mereka terapkan dalam usahanya.